Transcriptomic and morphophysiological evidence for a specialized human cortical GABAergic cell type. (September 2018) - Boldog, Eszter; Bakken, Trygve; Hodge, Rebecca; Novotny, Mark; Aevermann, Brian; Baka, Judith; Bordé, Sándor; Close, Jennie; Diez-Fuertes, Francisco; Ding, Song-Lin; Faragó, Nóra; Kocsis, Ágnes; et al.
Abstract We describe convergent evidence from transcriptomics, morphology, and physiology for a specialized GABAergic neuron subtype in human cortex. Using unbiased single-nucleus RNA sequencing, we identify ten GABAergic interneuron subtypes with combinatorial gene signatures in human cortical layer 1 and characterize a group of human interneurons with anatomical features never described in rodents, having large 'rosehip'-like axonal boutons and compact arborization. These rosehip cells show an immunohistochemical profile (GAD1+ CCK+, CNR1– SST– CALB2– PVALB– ) matching a single transcriptomically defined cell type whose specific molecular marker signature is not seen in mouse cortex. Rosehip cells in layer 1 make homotypic gap junctions, predominantly target apical dendritic shafts of layer 3 pyramidal neurons, and inhibit backpropagating pyramidal action potentials in microdomains of the dendritic tuft. These cells are therefore positioned for potent local control of distal dendritic computation in cortical pyramidal neurons. The authors use single-nucleus RNA-seq to identify 10 GABAergic interneuron subtypes in human cortex layer 1. Molecular, morphological, and physiological evidence points to an emerging human cell type, the rosehip cell, not found in other species.